TGF-β1 overexpression in severe COVID-19 survivors and its implications for early-phase fibrotic abnormalities and long-term functional impairment - Alfaro, Enrique; Casitas, Raquel; Díaz-García, Elena; García-Tovar, Sara; Galera, Raúl; Torres-Vargas, María; Fernández-Velilla, María; López-Fernández, Cristina; Añón, José M.; Quintana-Díaz, Manuel; García-Río, Francisco; Cubillos-Zapata, Carolina (Frontiers in Immunology, 2024)
In post-COVID survivors, transforming growth factor-beta-1 (TGF-β1) might mediate fibroblast activation, resulting in persistent fibrosis. In this study, 82 survivors of COVID-19-associated ARDS were examined at 6-and 24-months post-ICU discharge. At 6-months, quantitative CT analysis of lung attenuation was performed and active TGF-β1 was measured in blood and exhaled breath condensate (EBC). At 6-months of ICU-discharge, patients with reduced DmCO/alveolar volume ratio exhibited higher plasma and EBC levels of active TGF-β1. Plasma TGF-β1 levels were elevated in dyspneic survivors and directly related to the high-attenuation lung volume. In vitro, plasma and EBC from survivors induced profibrotic changes in human primary fibroblasts in a TGF-β receptordependent manner. Finally, at 6-months, plasma and EBC active TGF-β1 levels discriminated patients who, 24-months post-ICU-discharge, developed gas exchange impairment. TGF-β1 pathway plays a pivotal role in the early-phase fibrotic abnormalities in COVID-19-induced ARDS survivors, with significant implications for long-term functional impairment.